2014
DOI: 10.1590/1415-52732014000500009
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality assessment indexes

Abstract: A B S T R A C TVarious indices and scores based on admittedly healthy dietary patterns or food guides for the general population, or aiming at the prevention of diet-related diseases have been developed to assess diet quality. The four indices preferred by most studies are: the Diet Quality Index; the Healthy Eating Index; the Mediterranean Diet Score; and the Overall Nutritional Quality Index. Other instruments based on these indices have been developed and the words 'adapted', 'revised', or 'new version I, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 64 publications
0
10
0
7
Order By: Relevance
“…It has previously been reported that a diet lower in fat (20% vs.. 30% of total energy) may be associated with reduced risk of breast cancer in ER– females [ 90 ]. The diet quality indices in this review that were associated with a reduced risk of breast cancer were the MDS, HEI, DASH, and RFS, or variations thereof, and, although these indices do not typically quantify total fat intake, they do score the type of fat, particularly saturated fat [ 91 ]. Higher intakes of saturated fats have been linked to an increased risk of breast cancer [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that a diet lower in fat (20% vs.. 30% of total energy) may be associated with reduced risk of breast cancer in ER– females [ 90 ]. The diet quality indices in this review that were associated with a reduced risk of breast cancer were the MDS, HEI, DASH, and RFS, or variations thereof, and, although these indices do not typically quantify total fat intake, they do score the type of fat, particularly saturated fat [ 91 ]. Higher intakes of saturated fats have been linked to an increased risk of breast cancer [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, European countries also use the MedDietScore (MDS), PREDIMED Mediterranean Diet Score, (P-MDS), and Dutch Healthy Diet-Index (DHDI), among others [8]. Other countries such as Brazil and Singapore, have reported using the Healthy Diet Indicator, the Diet Quality Index, and Overall Nutritional Quality Index [17,18]. Both DQS and DDS are cost-effective, non-invasive tools to assess dietary patterns within a population and can be used to orientate public health policies, communicate risk and targeted preventive lifestyle or pharmacological interventions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Diet quality (DQ) is a central parameter of dietary pattern research. The DQ concept is used to evaluate the diets of populations or individuals [10][11][12], assess the effectiveness of nutrition interventions [13] and expose diet-disease associations [14]. Arising largely from epidemiological studies, the DQ concept encapsulates descriptors related to nutrition, such as, "healthy diet, balanced diet, nutritious food, etc."…”
Section: Introductionmentioning
confidence: 99%
“…Recognised complexities emerging from nutrition epidemiology [19][20][21] have exposed the necessity for a more integrated approach utilising diet quality indices (DQIs) to examine the 'whole of diet' effects [22]. Several reviews [12,14,[23][24][25][26][27] have identified multiple DQIs that vary in design and the referent food or nutrient characteristics. DQIs tend to be applied in epidemiological studies to establish diet-disease links, characterise patterns of food consumption or evaluate adherence to country-specific dietary guidelines [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%